Analisis Kesulitan Membaca Permulaan Siswa Sekolah Dasar - Khofiyah, Anisa Nidaul; Frestava, Vitnes Ingkaning; Azifa, Linda Rustiya Nur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Early reading difficulties in elementary school students are an important problem in the educational process. The aim of this research is to determine the factors that influence initial reading difficulties, as well as the types of difficulties students face in initial reading based on several related studies. Various factors such as the environment, psychology, and internal maturity of students can be the main causes of reading difficulties. Types of difficulties include a lack of understanding of letters, difficulty pronouncing words, and limitations in reading sentences or paragraphs. This research uses qualitative methods through literature study. The data analysis technique used in this research is content analysis. The results illustrate the various difficulties experienced by students, including difficulties in recognizing letters, difficulties in pronouncing, and difficulties in reading words, syllables, sentences, as well as aspects of incorrect pronunciation. solving initial reading difficulties includes the important role of teachers in providing learning that suits students' needs, parental support in providing motivation, as well as creating a social environment that supports the process of learning to read. By overcoming initial reading difficulties, it is hoped that elementary school students can develop their reading skills effectively to support better academic development